Revolutionizing Salinized Farmland: How Salt-Controlled Irrigation Transforms Microbial Diversity and Soil Organic Matter in a Salt-Alkali Soil - Xu Yang; Ruihong Yu; Guanglei Yu; Yansong Bai; Muhan Li; Zeyuan Liu; Shen Qu; Ping Miao; Hongli Ma; Tao Zhang; Yonglin Jia (Agronomy)
China is one of the countries most seriously affected by soil salinization, while the impact of salt-controlled irrigation on the relationship between soil dissolved organic matter (DOM) and microbial in farmland affected by salinization remains largely unexplored. We conducted a comprehensive survey of soil DOM and a microbial survey of Ordos’s salinized farmland in China before and after salt-controlled irrigation. Our findings reveal a reduction of 18.4 mg/L in surface soil (0–10 cm) DOC following irrigation, whereas the subsurface soil (20–40 cm) DOC increased by 20.7 mg/L. Moreover, irrigation led to an increase in the aromaticity and humification of the soil, with the salt content of the subsurface soil rising from 2.7 to 3.7 mg/g. Additionally, the total dissolved solids (TDS) in the drained water were 2463 mg/L higher than in the irrigation water (1416.3 mg/L). This suggests that the DOM and salts from the surface soil either leached into deeper layers or were lost via runoff. Furthermore, SEM analysis and a Mantel test revealed that microbial composition significantly influenced soil DOM contents, especially increased levels of Marmoricola and MND1, which are associated with decomposing organic matter and may contribute to the leaching of soil DOM in deep layers following irrigation.